Excessive Extrapolation and the Allocation of 401(k) Accounts to Company Stock - Benartzi, Shlomo (Journal of Finance, 2001)
ABSTRACT About a third of the assets in large retirement savings plans are invested in company stock, and about a quarter of the discretionary contributions are invested in company stock. From a diversification perspective, this is a dubious strategy. This paper explores the role of excessive extrapolation in employees' company stock holdings. I find that employees of firms that experienced the worst stock performance over the last 10 years allocate 10.37 percent of their discretionary contributions to company stock, whereas employees whose firms experienced the best stock performance allocate 39.70 percent. Allocations to company stock, however, do not predict future performance.